PENGARUH VIDEO ANIMASI PEMBELAJARAN JARAK JAUH TERHADAP KEMAMPUAN BERPIKIR LOGIS ANAK USIA DINI - Putri Ayu Maharani; Elisa Novie Novie Azizah; Susdarwati Susdarwati (Universitas Islam Lamongan, 2021)
Abstract This study aims to determine the effect of distance learning animation videos on the logical thinking skills of group A children in TK Dharna Wanita Padas - Ngawi. The research used is quantitative type. The data collection method used in this research is the research method used in this research is pre-experimental design and single group pre-test and post-test design. This is because there is no parallel class at school, so that 21 children were selected as research subjects who came from TK Dharna Wanita Padas, Ngawi. The data analysis technique used is to use the t-test to perform parameter statistics on small correlated samples. The data collection method uses participant observation. Based on the results of data analysis with a significance level of 5%, it was obtained tcount > ttable (4.3 > 1.7). This can be interpreted that the alternative hypothesis (Ha) can be accepted, so the distance learning animation video (has a significant effect) or it can be said to be an effective way of the logical thinking ability of group A children TK Dharna Wanita Padas, Ngawi.